PENGARUH PENGGUNAAN OLI MINERAL, SEMI SINTETIK DAN FULL SINTETIK TERHADAP PENINGKATAN SUHU MESIN MOTOR 4 LANGKAH MANUAL BERKAPASITAS 125 CC - Muhamad Ikmal Fawaz; Anggara Sukma Ardiyanta; Emdi Ramadana Putra (Universitas Negeri Surabaya, 2025)
This study aims to analyze the effect of mineral, semi-synthetic, and full-synthetic engine oils on temperature rise in a 125cc four-stroke motorcycle engine. A quantitative experimental method was applied using three lubricants: AHM MPX 1 (mineral), Mobil Super Moto (semi-synthetic), and AHM SPX 1 (full-synthetic). Tests were conducted on a Honda Supra X 125cc KPH-type engine running at 2000 rpm for 5 minutes from an initial temperature of 40°C. Temperature was measured using a Habotest HT-9829 digital infrared thermometer, while engine speed was monitored with a digital tachometer. One-way ANOVA analysis produced an F-value of 50.293 and a p-value of 0.000 (p < 0.05), indicating significant differences among oil types. The full-synthetic oil yielded the lowest average temperature rise (37.6°C), followed by semi-synthetic (40.5°C) and mineral oil (42.5°C). The results show that lubricant type affects thermal stability, with full-synthetic oil providing superior temperature control.